Numerical analysis of flow characteristics of the oil-water mixture in stratified-annular horizontal pipe - Erizon, Nelvi; Jasman, Jasman; Irzal, Irzal; Aldio, Muhammad Fikhri; Saputra, Aprizal; Tin, Chau Trung (Teknomekanik, 2022)
The loss of oil fluid flow in the piping system in the petroleum industry due to friction is the cause of low efficiency. To reduce friction loss, the viscosity of petroleum can be lowered by adding water as a mixture. Actually, the flow loss in a piping system is influenced by several factors including flow pattern, fluid type, flow velocity, flow pressure and pipe diameter. This study aims to determine the effect of flow patterns on changes in velocity in the two-phase flow of oil and water in a piping system. This numerical analysis research was carried out using Fluent 6.2 software with variations in the velocity of the oil-water mixture: 0.2, 0.4 and 0.6 m/s. The simulation results show that the greatest pressure loss occurs at a fluid velocity of 0.6 m/s where the flow is stratified mixed. While the smallest pressure loss at a mixture velocity of 0.2 m/s when the flow is stratified smooth. From the results of the study, it can be concluded that the increase in fluid flow velocity has a positive correlation with the increase in the value of flow losses in the pipe.